Biallelic Mutations in DNAJB11are Associated with Prenatal Polycystic Kidney Disease in a Turkish Family - ARMAN, AHMET; GEÇKİNLİ, BİLGEN BİLGE; ALAVANDA, CEREN; DELİL, KENAN; SÖYLEMEZ, MEHMET ALİ; ATA, PINAR (KARGER, 2021)
Polycystic kidney disease (PKD) is a life-threatening condition resulting in end-stage renal disease. Two major forms of PKD are defined according to the inheritance pattern. Autosomal dominant PKD (ADPKD) is characterized by renal cysts, where nearly half of the patients suffers from renal failure in the 7th decade of life. Autosomal recessive PKD (ARPKD) is a rarer and more severe form presenting in childhood. Whole-exome sequencing (WES) analyses was performed to investigate molecular causes of the disease in the fetus. In this study, we present 2 fetuses prenatally diagnosed with PKD in a consanguineous family. WES analysis of the second fetus revealed a homozygous variant (c.740+1G>A) in DNAJB11 which is related to ADPKD. This study reveals that DNAJB11 biallelic mutations may cause an antenatal severe form of ARPKD and contributes to understanding the DNAJB11-related ADPKD phenotype. The possibility of ARPKD due to biallelic mutations in ADPKD genes should be considered in genetic counseling.
Keywords: DNAJB11; Whole-exome sequencing; Nephrology; Genetic counseling; Polycystic kidney disease